(untitled) (Mongolian Journal of International Affairs, 2025)
The article set out to find answers to two main questions. First, to find out if there is a link or relationship between the environment and peace and security? And, second, to ascertain the impacts of environmental crises on human life and progress? These two questions were answered. In the first case, the paper found out that there is a credible link between the environment and peace and security. In environments where there are conflicts and crises, it was found out that there is usually a lack or an absence of peace and security. In such environments were wars and conflicts are ongoing, it was found out that there are also adverse effects on the environment itself, such as soil, water and air pollution from the discharge of ammunition and bombs for instance. In the second case, the paper found out that environmental crises has a negative impact on human lives and stifles progress. In environments with poor sanitation and in an unhygienic state, human creativity and ingenuity is held back and insecurity blossoms. The paper ended with several recommendations among which is the creation or development of more binding environmental treaties with the aim of securing, protecting and preserving our environment for future generations to enjoy it in peace and security.